Progress in the Chemistry of Organic Natural Products 110 Cheminformatics in Natural Product Research - Kinghorn, A. Douglas; Falk, Heinz; Gibbons, Simon; Kobayashi, Jun'ichi; Asakawa, Yoshinori; Liu, Ji-Kai (Progress in the Chemistry of Organic Natural Products, 2019)
The book summarizes important aspects of cheminformatics that are relevant for natural product research. It highlights cheminformatics tools that help to match natural products with their respective biological targets or off-targets, and discusses the potential and limitations of this approach.